Probiotic Lactobacillus johnsonii Reduces Intestinal Inflammation and Rebalances Splenic Treg/Th17 Responses in Dextran Sulfate Sodium-Induced Colitis - Hao-Yu Liu; Shicheng Li; Kennedy Jerry Ogamune; Peng Yuan; Xinyu Shi; Wael Ennab; Abdelkareem A. Ahmed; In Ho Kim; Ping Hu; Demin Cai (Antioxidants)
Inflammatory bowel disease (IBD), a chronic inflammatory disorder of the gastrointestinal tract, is frequently complicated by extraintestinal manifestations such as functional hyposplenism. Increasing evidence highlights its pathogenesis as a multifactorial interplay of gut dysbiosis, intestinal barrier dysfunction, and dysregulated immune responses. While probiotics, particularly Lactobacillus spp., have emerged as potential therapeutics for IBD, restoring intestinal homeostasis, their systemic immunomodulatory effects remain underexplored. Here, we investigated the protective role of Lactobacillus johnsonii N5 in DSS-induced colitis, focusing on inflammation inhibition and splenic T cell regulation. Pretreatment with L. johnsonii N5 significantly attenuated colitis severity, as evidenced by preserved body weight, reduced disease activity index, and prevention of colon shortening. N5 suppressed colonic pro-inflammatory factors such as TNF-α, Il-1b, Il-6, and CXCL1, while elevating anti-inflammatory IL-10 at both mRNA and protein levels. Transcriptomic analysis of the spleen revealed that N5 mediated the downregulation of inflammatory pathways, including the IL-17 and TNF signaling pathways, as well as the HIF-1 signaling pathway, and modulated the metabolic pathway of oxidative phosphorylation. Flow cytometry analysis demonstrated that N5 rebalanced splenic Treg/Th17 responses by expanding the Treg population and reducing the production of IL-17A in Th17 cells. Notably, Th17-associated IL-17A positively correlated with intestinal pro-inflammatory mediators, emphasizing the role of Th17 cells in driving colitis. In contrast, splenic Treg abundance positively correlated with colonic IL-10 levels, suggesting a link between systemic immune regulation and intestinal anti-inflammatory responses. Our study underscores the therapeutic potential of targeting gut–immune crosstalk through probiotics, thereby offering valuable insights for developing live bacterial-based interventions for IBD and other inflammatory disorders.